Politeness in East Asia - Kadar, Daniel Z., 1979-; Mills, Sara, 1954- (Cambridge : Cambridge University Press, 2011)
'We use politeness every day when interacting with other people. Yet politeness is an impressively complex linguistic process, and studying it can tell us a lot about the social and cultural values of social groups or even a whole society, helping us to understand how humans'encode' states of mind in their words. The traditional, stereotypical view is that people in East Asian cultures are indirect, deferential and extremely polite - sometimes more polite than seems necessary. This revealing book takes a fresh look at the phenomenon, showing that the situation is far more complex than these stereotypes would suggest. Taking examples from Japanese, Korean, Chinese, Vietnamese and Singaporean Chinese, it shows how politeness differs across countries, but also across social groups and subgroups. The first comprehensive study of the subject, this book is essential reading for those interested in intercultural communication, linguistics and East Asian languages'--
Machine generated contents note: Foreword Francesca Bargiela-Chiappini; 1. Introduction Diel Z. K{u2864} and Sara Mills; Part I. Politeness in East Asia - Theory: 2. Politeness and culture Sara Mills and Diel Z. K{u2864}; 3. Honorifics: the cultural specificity of a universal mechanism in Japan Barbara Pizziconi; 4. Methodological issues in East Asian politeness research Yuling Pan; 5. Intercultural communication and East Asian politeness Stefanie Stadler; Part II. Politeness in East Asia - Practice: 6. Politeness in China Diel Z. K{u2864} and Yuling Pan; 7. Politeness in Japan Michael Haugh and Yasuko Obana; 8. Politeness in Korea Alan Hyun-Oak Kim; 9. Politeness in Vietnam Grace Chye Lay Chew; 10. Politeness in Singapore Cher Leng Lee; 11. Epilogue Michael Haugh.
Includes bibliographical references and index.
Keywords: Politeness (Linguistics) -- East Asia; Grammar, Comparative and general -- Honorific; Interpersonal relations -- East Asia; LANGUAGE ARTS & DISCIPLINES / Linguistics / Semantics; East Asia -- Languages